(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Antenatal care (ANC) is essential for reducing maternal and neonatal morbidity and mortality. However, in rural areas of South Punjab, Pakistan, ANC utilization remains markedly low despite the availability of public health services. Nurses, being the first-line providers of maternal healthcare in rural settings, are uniquely positioned to identify barriers affecting ANC uptake. Objective: To explore the socio-cultural, economic, and health system barriers influencing ANC utilization in rural tehsils of South Punjab from the nursing perspective. Methods: A qualitative descriptive study was conducted from March to July 2025 in three rural tehsils, Lodhran, Muzaffargarh, and Layyah. Using purposive sampling, 20 registered nurses working in Basic Health Units (BHUs) and Rural Health Centers (RHCs) with at least one year of ANC experience were interviewed through semi-structured, in-depth interviews. Data were transcribed verbatim and analyzed thematically using Braun and Clarke’s six-step framework to identify emerging patterns and themes. Results: Four major themes and ten subthemes emerged: (1) Socio-cultural barriers including restricted female autonomy, cultural misconceptions, and privacy concerns; (2) Economic and geographic constraints such as poverty, long distances, and lack of transport; (3) Health system limitations including staff shortages, infrastructure deficiencies, medicine unavailability, and negative staff attitudes; and (4) Knowledge and awareness gaps highlighting low literacy, reliance on traditional birth attendants, and minimal male involvement in maternal health decisions. Nurses emphasized that these interconnected factors collectively restrict women’s access to consistent ANC and contribute to delayed care-seeking behaviors. Conclusion: Barriers to ANC utilization in rural South Punjab are multifactorial, rooted in gender norms, economic hardship, and systemic inadequacies. From a nursing perspective, improving ANC uptake requires culturally sensitive health education, community-based awareness programs, stronger nurse-patient communication, and facility-level reforms to ensure privacy and supply consistency. Nurse empowerment and male-inclusive community interventions can play a pivotal role in enhancing maternal health outcomes in rural Pakistan.